Public-Private Partnership and Early Childhood Education in Kasese District, Uganda. - Kategaya, Raymond Mwesigye; Adyanga, Akena Francis; Ocan, Johnson (Kabale University, 2024)
The article’s main purpose was to investigate the relationship between public-private partnership (PPP) and early childhood education in Kasese District, Uganda. The main objectives of the study were to establish the role played by public-private partnerships in making certain that children develop numerical skills and expressive communication abilities. The study was conducted through an Ex Post Facto design study design. The target population of the study was stakeholders for early childhood education in Kasese District, Western Uganda. To ensure fair representation, research subjects were selected from each stratum of stakeholders. The scholar thus used stratified and, later on, random sampling techniques. The sample selected had 312 respondents from an estimated total number of 1.417 ECD stakeholders in Kasese District. Primary data was collected by administering a questionnaire that was designed on a 5-point Likert Scale, ranging from strongly agree to strongly disagree. Face-to-face interviews and an observation checklist were also used in the collection of data. Data collected was presented and analyzed with frequency distribution and percentages while the corresponding hypothesis was tested with Chi-square statistic at 0.05 alpha levels. It was found the PPP in ECDs helped in the improvement of numeracy among children. For instance, stakeholders’ work helped in improving children’s counting of fingers on one hand or even copying and drawing shapes amongst young ones. Similarly, respondents indicated that Policy Guideline Formulation due to PPP led children to sort objects by color and shape. Also, results showed that PPP in ECD enhanced communication ability whereby children were able to put up two words together as per caregiver guidance. It also led a child to pay attention to a simple story being narrated and thereafter answer questions from the account. Similarly, it was also found that Institutional Factors for PPP supported expressive ability in children in that they were in a position to follow a simple command. Besides, the availability of suitable Home Environment Factors was also found to promote communication ability in children. Thus, the study concluded that public-private partnership plays a part in ensuring that children develop numerically.